Interdisciplinary treatment of the patient with adenoid cystic carcinoma of the Bartholin’s gland resulting in 15 years’ survival: a case report and review of literature - Nowak, Marek; Rycel, Magdalena; Szpakowski, Marian; Kulig, Andrzej; Sobotkowski, Janusz; Dziki, Adam (Menopause Review/Przegląd Menopauzalny, 2014)
Carcinoma of the Bartholin’s gland is very rare, comprises below 2% of Bartholin’s gland lesions and adenoid cystic carcinoma (ADC) is one of the most uncommon variants and accounts for 10-15% of Bartholin’s gland malignancies. There is no consensus on treatment of ADC of the Bartholin’s gland: reported cases were treated with local excision or vulvectomy with or without lymphadenectomy followed or not by radiotherapy. The survival of patients varies significantly, so we present a case of interdisciplinary treatment of ADC resulting in 15 years’ survival. The patient was initially treated with local excision, but the margins were not clear. Then vulvectomy, inguinal lymphadenectomy and adjuvant brachytherapy were performed resulting in 7 years free of the disease. Relapses were excised by abdominoperineal amputation of the rectum and distal part of the vagina with sigmoideostomy, excisions of local recurrences in vagina and metastasectomy of isolated lung metastases. The patient died manifesting multiple lung metastases 15 years after the initial diagnosis. Based on our experience and world literature, in cases of adenoid cystic carcinoma of the Bartholin’s gland, vulvectomy with or without lymphadenectomy should be considered as a treatment of choice and in patients with positive margin, surgery should be extended by adjuvant radiotherapy.